2010
DOI: 10.1111/j.1948-7134.2010.00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcription analysis of differentially expressed genes in insecticide-resistant Aedes aegypti mosquitoes after deltamethrin exposure

Abstract: Aedes aegypti mosquitoes are resistant to various insecticides, including pyrethroids, throughout Thailand. We previously reported that Ae. aegypti from Mae Wong district, Nakhon Sawan Province in north-central Thailand, were resistant to insecticides, including pyrethroids (deltamethrin and permethrin), organophosphates and carbamates, and that high levels of detoxification enzymes were present. In the present study we used the method of suppression by subtractive hybridization to determine differential expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Knowledge of the molecular mechanisms contributing to insecticide resistance is a basic requirement for overcoming this challenge. Importantly, the cuticle can impede the absorbance of insecticides, and several CPs are differentially expressed in insecticide resistant and susceptible strains in Culex pipiens pallens , Aedes aegypti , Anopheles gambiae and Anopheles stephensi . Recently, experimental evidence in C. pipiens pallens revealed that CPs can alter the sensitivity to deltamethrin.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the molecular mechanisms contributing to insecticide resistance is a basic requirement for overcoming this challenge. Importantly, the cuticle can impede the absorbance of insecticides, and several CPs are differentially expressed in insecticide resistant and susceptible strains in Culex pipiens pallens , Aedes aegypti , Anopheles gambiae and Anopheles stephensi . Recently, experimental evidence in C. pipiens pallens revealed that CPs can alter the sensitivity to deltamethrin.…”
Section: Introductionmentioning
confidence: 99%
“…Structural cuticular proteins (CPs) are the primary component of insect cuticle [ 1 , 2 ], and can form the Bouligand model to stabilize the complex structure of the cuticle in maintaining the elasticity and other physical properties of insects [ 3 ]. Evidence from Culex pipiens pallens L. [ 4 , 5 ], Aedes aegypti L. [ 6 ] and Bactrocera dorsalis Hendel [ 7 ] have indicated that some CPs are involved in the response to pesticides and arid and extreme temperature conditions. However, CPs vary greatly in number, sequence and structure within and between species [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both target site insensitivity and metabolic resistance have been identified as important mechanisms of insecticide resistance in Ae. aegypti, and several previous studies have investigated the specific genes involved in metabolic detoxification of insecticides in this mosquito species [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. This study aimed to disentangle the transcriptional basis of resistance to multiple insecticides in Ae.…”
Section: Introductionmentioning
confidence: 99%